ANALISIS BAHAYA KESEHATAN KERJA PADA PEKERJA INDUSTRI KONVEKSI DI KRENDANG, JAKARTA - Yusuf, Mega Yulian; Raihan, Muhammad Fajri; Erisca, Rehvynanda; Maheswari, Moza Adisty; Sosronegoro, Salsabila Aliyah; Widjaya, Muchamad Osama; Narottama, Rakha Mahisha; Nurdianti, Dita Suci; Zaina, Nashita Amira; Taroreh, Indah Rahmadany; Gabrielle, Laurentia; Lestari, Ade Dwi (Jurnal Pengabdian Masyarakat Trimedika, 2025)
This study analyzed work hazards in a small convection industry owned by Mr. G in Krendang Village, West Jakarta.  The research methods included interviews with the business owner and five workers, and measurement of work environment parameters such as lighting, noise and vibration using a measuring application.  Health risk analysis was conducted based on a risk matrix (4x4) that considers probability and consequence. The results showed several health risks, including musculoskeletal disorders due to repetitive movements, dust exposure, and heat. The highest risk is fatigue due to long working hours (medium-high). In conclusion, the convection industry has several occupational health risks that need to be addressed, especially by improving lighting, reducing noise and vibration, and implementing adequate rest periods.  Recommendations include educating workers about ergonomic work postures and the use of personal protective equipment.